Preparation, characterization, and enhanced antimicrobial activity: quercetin-loaded PLGA nanoparticles against foodborne pathogens - Arasoglu, Tulin; Derman, Serap; Mansuroglu, Banu; Uzunoglu, Deniz; Kocyigit, Busra; Gumus, Busra; Acar, Tayfun; Tuncer, Burcu (Tubitak Scientific & Technological Research Council Turkey, 2017)
The use of quercetin as a bioflavonoid is becoming increasingly common in food industries even though poor water solubility, instability, absorption, and permeability have limited its application. The oil-in-water single-emulsion solvent evaporation method to synthesize highly stable and soluble quercetin-encapsulated nanoparticles (NPs), in which the reaction yield, particle size, and polydispersity of the NPs are varied greatly within the process parameters of the synthesis method, has been optimized. NPs with different initial quercetin amounts were used to determine how the quercetin amount affected nanoparticle properties and antimicrobial efficiency. Listeria monocytogenes, Salmonella typhimurium, Escherichia coli, and Staphylococcus aureus were chosen as model bacteria due to their being foodborne pathogens. The results of antimicrobial activity evaluated by three different methods showed that the antimicrobial activity of both quercetin NPs and free quercetin was effective on gram-positive strains (L. monocytogenes and S. aureus). Additionally, it was detected that Q31 NPs have more effective antimicrobial activity than other synthesized quercetin nanoparticles depending on the amount of substance and release. Furthermore, on the basis of assessing the antibacterial effects by scanning electron microscopy, it was detected that bacteria cells lost their integrity and became pale with the release of cytoplasm and decomposed after treatment with Q31 NPs.
Keywords: Antimicrobial activity; nanoparticle; pathogens; PLGA; quercetin; BIODEGRADABLE NANOPARTICLES; PARTICLE-SIZE; LISTERIA-MONOCYTOGENES; PHENOLIC-COMPOUNDS; DRUG-DELIVERY; STAPHYLOCOCCUS; HYDROCHLORIDE; EXTRACT; AGENTS; Life Sciences & Biomedicine - Other Topics